Impact of Inspection Strategy on Repairing Cost of Distribution Transformer - Patel, Nirav J.; Dhimar, Nikunj J.; Solanki, Pratik D; Patel, Jay A (Asian Journal of Electrical Sciences, 2018)
The Objective of the paper is to do Proper Inspection procedure of failed distribution transformer will reduce the repairing cost. Methods and Statistical analysis includes steps to do external and Internal Inspection with care so that it will not add any pointless expense. This paper highlights the Life cycle of failed distribution transformer and foremost objectives of Inspection which is directly affecting the procedure of repairing and its overall repairing cost. Findings of the paper convey that Inspection of failed distribution transformer is a planned technical extent which will affect directly to repair cost. The project can be applied for Proper Inspection practice will absolutely reduce the repair cost and over all transformer repairing expense of DISCOM.